EKSPLORASI PERSEPSI MAHASISWA MENGENAI PENGINTEGRASIAN KEAHLIAN STORY TELLING DALAM PEMBELAJARAN BAHASA INGGRIS DI SEKOLAH KEPARIWISATAAN - Kadek Wiramarta (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2022)
With the emerging role of stories in supporting the value of a tourist attraction, a tourism practitioner is required to be able to convey an engaging story regarding the tourism destination. Therefore, Vocational Higher Education is expected to help educating prospective tourism practitioners to meet this demand. This study aims to discuss on how to implement story telling in the English learning process and explore students' perceptions on this specific practice. For this reason, the researcher implemented story telling activities for 4 meetings in a class consisting of 21 people and then collected data afterwards. This research uses qualitative and quantitative approaches to obtain comprehensive results. This study found that in integrating story telling into English learning, various methods can be used to ensure that the learning objectives can be achieved. Students think that it is important to integrate story telling in learning English. In addition, story telling is considered useful for students in the professional world. It also reveals that all students will implement and use the knowledge in this learning process in the professional work later. However, it should also be noted that students experience various difficulties in the learning process while using story telling in tourism. This research is expected to provide further references on using story telling for Englosh for Tourism in tourism vocational higher education.